Lack of rewarding effects of a soluble epoxide hydrolase inhibitor TPPU in mice: Comparison with morphine - Xiayun Wan; Yuko Fujita; Lijia Chang; Yan Wei; Li Ma; Gerile Wuyun; Yaoyu Pu; Bruce D. Hammock; Kenji Hashimoto (Wiley, 2020)
Abstract Aim Although opioids have been used as treatment of neuropathic pain, opioids have abuse potential in humans. Since soluble epoxide hydrolase (sEH) in the metabolism of polyunsaturated fatty acids plays a key role in the pain, sEH inhibitors would be promising new therapeutic drugs for neuropathic pain. In this study, we examined the effect of the sEH inhibitor TPPU on rewarding effects in mice using the conditioned place preference (CPP) paradigm. Methods The rewarding effects of morphine (10 mg/kg) and TPPU (3, 10, or 30 mg/kg) in mice were examined using CPP paradigm. Furthermore, the effect of TPPU (30 mg/kg) on morphine‐induced rewarding effects was examined. Results TPPU (3, 10, or 30 mg/kg) did not increase CPP scores in the mice whereas morphine significantly increased CPP scores in the mice. Furthermore, pretreatment with TPPU did not block the rewarding effects of morphine in the mice, suggesting that sEH does not play a role in the rewarding effect of morphine. Conclusion This study suggests that TPPU did not have rewarding effects in rodents. This would make sEH inhibitors potential therapeutic drugs without abuse potential for neuropathic pain.